Mission Possible? Institutional Family-School-Community Partnership Practices and Parental Involvement in Hungarian Majority and Minority Schools in Three Central and Eastern European Countries - Gabriella Pusztai; Katinka Bacskai; Tímea Ceglédi; Zsófia Kocsis; Megumi G. Hine (Social Sciences)
Decades of research suggest that higher levels of parental education are related to more active and effective parental involvement (PI) practices. At the same time, schools’ policies and practices facilitate family-school-community partnerships (FSCPs) to support students in attaining successful outcomes. However, it is unclear which school policies are effective in equitably involving parents with lower educational attainment. This study aims to examine the relationships between different types of FSCP practices of Hungarian majority and minority schools in Central and Eastern Europe (CEE) and create more equitable experiences for parents with lower educational attainment. We formulated the following hypotheses: H1. Higher levels of parental education relate to more active home-based and school-based parental involvement. H2. Parent educational attainment relates to parents’ perceptions of FSCP practices. H3. Parents’ perceptions of FSCP have a stronger relationship to PI than individual student and parent characteristics. The study included parents of Hungarian primary and middle school students in three CEE countries (N = 1002). Our findings suggest that parents with lower educational attainment perceive community development policies and special support as more significant compared to parents with higher educational attainment. Moreover, parents’ perceptions of FSCP practices have a stronger relationship to PI than individual factors. To create a more equitable experience for families, it is proposed that demand-driven practices be developed in schools.